EKSPRESI WAJAH DALAM KARYA SENI GRAFIS - IFWALDI MALIK, Dr. Budiwirman, M.Pd, Drs. Idran Wakidi (Serupa The Journal of Art Education, 2014)
This work generated after passing through various processes and inspired many of the things that often authors see everyday and of the search process from a variety of books and also through other media. Of the various search results, the authors make the work with the title: 1), "joy" 2), "Crying" 3), "Crying in solitude" 4), "Sad" 5), "Restraining sadness" 6), "Angry "7)," Smile "8)," Scorn "9)," Shocked "10)," Fear "from the titles of these works, the authors create works that show the daily expression of desire As the authors is that the work can be understood by anyone. and later be useful for art lovers and writers themselves.Kata kunci : Seni Grafis, Ekspresi Wajah, Relief Print